Ceramic composite material and method for producing the same

By adding nano-ZrC and nano-ZrN ceramic powders to MgO·1.1Al2O3 powder and employing a two-step sintering method, a ceramic composite material with excellent hardness and strength was prepared, solving the problem of insufficient hardness in non-stoichiometric magnesium aluminum spinel ceramics, making it suitable for high-radiation environments.

CN117776684BActive Publication Date: 2025-11-07王帅 +5
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311505829.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2025-11-07
Estimated Expiration
2043-11-13

AI Technical Summary

Technical Problem

While existing non-stoichiometric magnesium aluminum spinel ceramics have excellent resistance to radiation damage, their low hardness makes them unsuitable for use in high-radiation environments.

Method used

A ceramic composite material was prepared by combining MgO·1.1Al2O3 powder with nano-ZrC ceramic powder and nano-ZrN ceramic powder through a two-step sintering method. The hardness and strength were improved by utilizing the refined grain size of the nano-powder and the Zr(C,N) solid solution generated by the reaction.

Benefits of technology

It significantly improves the hardness and strength of ceramic composite materials, meeting the requirements for use in high-radiation environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of nuclear energy structural materials, and specifically discloses a ceramic composite material and a preparation method thereof. The ceramic composite material comprises the following components: MgO.1.1Al2O3 powder and zirconium ceramic powder accounting for 5-10% of the volume of the MgO.1.1Al2O3 powder; the zirconium ceramic powder comprises the following components in volume percentage: 45-55% of nano ZrC ceramic powder and the balance of nano ZrN ceramic powder; and the preparation method is as follows: firstly, sintering the MgO.1.1Al2O3 powder and 55-65 Vol.% of the zirconium ceramic powder to obtain an initial ceramic composite material, and then crushing the initial ceramic composite material and mixing and sintering the remaining zirconium ceramic powder to obtain the ceramic composite material. The ceramic composite material has the advantages of high hardness and strength.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of nuclear energy structural materials, and more particularly to a ceramic composite material and a preparation method thereof. BACKGROUND

[0002] Nuclear materials are a key link in nuclear facilities, and the performance of the materials directly restricts the safety and service life of the nuclear equipment. Therefore, the development of nuclear materials largely determines the maturity of the development of nuclear equipment. Due to the harsh use environment of nuclear materials, for example, some key nuclear materials usually need to withstand high pressure, high temperature, high irradiation and strong corrosion during use, and therefore the nuclear materials need to meet various performance requirements such as physical performance, chemical performance, anti-irradiation performance and the like. In addition, the manufacturing, processing difficulty and economic cost of the nuclear materials are also taken into consideration, which become one of the conditions restricting the development and application of nuclear materials.

[0003] Among many materials, ceramic materials have a large number of applications in many key industries such as aerospace, new energy, laser, biological engineering and marine engineering due to their good rigidity, high strength, high temperature resistance, good thermal shock resistance and corrosion resistance. Some ceramic materials also have excellent anti-irradiation performance, and some special ceramic materials can even absorb neutrons. These advantages make ceramic materials more advantageous in the harsh nuclear industrial environment of high radiation, high pressure and high temperature.

[0004] Magnesium aluminate spinel ceramic (MgAl2O4) with a cubic structure exhibits good resistance to thermal conductivity reduction and strength degradation after irradiation: the strength of MgAl2O4 increases after neutron irradiation; at temperatures of 925K and 1100K, the fracture toughness and hardness of single-crystal spinel change little or almost not at all. Therefore, even though magnesium aluminate spinel ceramic is not a high-strength, high-thermal-conductivity ceramic, its good performance under irradiation makes it the most promising ceramic material for application in fusion reactors.

[0005] When the ratio of MgO and Al2O3 in MgAl2O4 is not 1:1, it is called non-stoichiometric magnesium aluminate spinel, and the chemical formula is MgO·nAl2O3. Single-phase spinel exists from n=0.667 (MgO-rich) to n=3.5 (Al2O3-rich). Related research has found that when n increases, the anti-irradiation damage capability and optical properties (visible light transmittance) of non-stoichiometric magnesium aluminate spinel are significantly improved. However, it also brings some other problems, such as larger grain size, lower density and lower hardness of the material; specifically, for example, when n increases from 0.667 to 1.5, the grain size increases from 10 μm to 70 μm, and the hardness decreases from 21 GPa to 18 GPa.

[0006] Therefore, it is necessary to provide a material so that the non-stoichiometric magnesium aluminate spinel has excellent radiation damage resistance and good hardness. SUMMARY

[0007] In order to improve the hardness of the Al2O3-rich non-stoichiometric magnesium aluminate spinel, the application provides a ceramic composite material and a preparation method thereof.

[0008] In a first aspect, the application provides a ceramic composite material, which adopts the following technical scheme:

[0009] The ceramic composite material comprises the following components: MgO*1.1Al2O3 powder and zirconium ceramic powder accounting for 5-10% of the volume of the MgO*1.1Al2O3 powder.

[0010] The zirconium ceramic powder comprises the following components in volume percentage: 45-55% of nano ZrC ceramic powder and 45-55% of nano ZrN ceramic powder.

[0011] By adopting the above technical scheme, the nano ceramic composite material with improved hardness and strength is prepared. The possible reason is that in the above scheme, the nano ZrC ceramic powder and the nano ZrN ceramic powder are selected, and the particle size of the nano powder is small. Therefore, when the nano powder is mixed with the MgO*1.1Al2O3 powder to prepare the ceramic composite material, it has a significant effect of refining the grains, promotes the densification of the ceramic material during sintering, and achieves the purpose of improving the hardness of the ceramic composite material. In addition, when the magnesium aluminate spinel ceramic is modified by adding a proper amount of nano ZrC ceramic powder and nano ZrN ceramic powder, the Zr(C,N) solid solution generated by the reaction of ZrC and ZrN can significantly improve the hardness and strength of the ceramic composite material. In addition, the added raw nano ZrC ceramic powder and nano ZrN ceramic powder will cause crystal phase migration and dispersion when mixed and sintered with the MgO*1.1Al2O3 powder, which will affect the crystal phase distribution. The ZrC grains, ZrN grains and MgO*1.1Al2O3 grains also affect each other, inhibit the transition of the grains, and further improve the hardness and strength of the ceramic material.

[0012] Optionally, the preparation method of the MgO*1.1Al2O3 powder comprises the following steps:

[0013] Step I: Mg(NO3)2*6H2O and Al(NO3)3*9H2O are mixed and stirred in a molar ratio of 1:(2-2.4) to obtain a clear nitrate solution; a citric acid solution is prepared for standby;

[0014] Step II, drop the citric acid solution into the nitrate solution, continuously stir at 55-65℃, adjust the pH value of the nitrate solution to 4.5-5.3, and dry to obtain a dry gel;

[0015] Step III, burn and crush the dry gel to obtain MgO·1.1Al2O3 precursor, calcine the MgO·1.1Al2O3 precursor at 700-800℃ for 1.5-2.5h to obtain MgO·1.1Al2O3 powder.

[0016] By adopting the above technical solution, high-purity nanoscale MgO·1.1Al2O3 powder is prepared to refine the crystal grains, make the mixing of raw materials more uniform, and improve the hardness and strength of the ceramic material.

[0017] Optionally, the drying temperature in step II is 140-155℃.

[0018] Optionally, the ambient temperature during burning of the dry gel in step III is 280-320℃.

[0019] Optionally, the particle size D of the nano ZrC ceramic powder is 0<D<30nm, and the purity is ≥99.9wt%. ZrC ZrC

[0020] Optionally, the particle size D of the nano ZrN ceramic powder is 0<D<100nm, and the purity is ≥99.9wt%. ZrN ZrN

[0021] By adopting the above technical solution, in addition to providing nanoscale additional raw materials, the two raw materials have a certain gradation in particle size, making the mixing of each raw material more uniform, so as to form a ceramic material with stable performance after sintering.

[0022] In a second aspect, the application provides a preparation method of the above ceramic composite material, which adopts the following technical solution: a preparation method of the above ceramic composite material, comprising the following steps:

[0023] Step S1, uniformly mix all MgO·1.1Al2O3 powder and 55-65Vol.% zirconium ceramic powder, and then press to obtain an initial ceramic green body;

[0024] Step S2, sinter the ceramic green body to obtain an initial ceramic composite material;

[0025] Step S3, crush the initial ceramic composite material into powder, add the remaining 35-45Vol.% zirconium ceramic powder, mix uniformly, and then press to obtain a reset ceramic green body;​​​​

[0026] Step S4, sintering the reset ceramic blank to obtain a ceramic composite material.

[0027] By adopting the technical scheme, the initial composite material is obtained through the first sintering, that is, the process of grain refinement, hardness and strength improvement of the magnesium aluminate spinel ceramic is realized after steps S1 and S2. Then, the process of grain refinement, hardness and strength improvement of the magnesium aluminate spinel ceramic is performed again through S3 and S4. It is found that the method can significantly improve the hardness and strength of the ceramic composite material compared with the first sintering method. The reason may be that the hardness and strength of the magnesium aluminate spinel ceramic are strengthened once after the first sintering; after crushing, the powder with new surface components is formed to perform new reaction, which has the effect of densifying the ceramic composite material; in addition, the reaction is a solid phase reaction, and there is a problem of uneven mixing of raw materials, and after mixing the zirconium ceramic powder and the magnesium aluminate spinel powder modified once, the mixing uniformity of the zirconium ceramic powder and the magnesium aluminate spinel powder is significantly improved, so that the reaction approaches the process of liquid phase reaction, and the strengthening effect of the zirconium ceramic powder is significantly enhanced, so that the hardness and strength of the ceramic composite material are finally significantly improved.

[0028] Optionally, the pressure applied during the pressing treatment in step S1 is 300-400 MPa; the pressure applied during the pressing treatment in step S3 is 300-400 MPa.

[0029] Optionally, the sintering process in step S2 includes calcining the ceramic blank at 1600-1800℃ for 1.5-2.5h; the sintering process in step S4 includes calcining the ceramic blank at 1600-1800℃ for 1.5-2.5h.

[0030] In summary, the present application has the following beneficial effects:

[0031] 1. The present application adds zirconium ceramic powder to MgO·1.1Al2O3 powder to obtain a ceramic composite material with excellent hardness; the zirconium ceramic powder is obtained by mixing nano ZrC ceramic powder and nano ZrN ceramic powder, and the two powders are selected to form a nano Zr(C,N) solid solution to play a role. The addition of zirconium ceramic powder changes the crystal phase distribution of the ceramic composite material, improves the density, and finally improves the hardness of the ceramic composite material.

[0032] 2. The ceramic composite material of the present application is prepared by a two-step sintering method to improve the material density and improve the strength.

[0033] 3、The zirconium ceramic powder is also added in batches during the two-step sintering when the ceramic composite material is prepared by the two-step sintering method; the method makes the zirconium ceramic powder and the MgO·1.1Al2O3 powder more uniformly mixed, and the surface contact probability of the MgO·1.1Al2O3 powder is greater, so that a more uniform crystal phase is formed after sintering, and a ceramic material with better hardness is obtained. DETAILED DESCRIPTION

[0034] The application will be further described in detail below in conjunction with examples, and it is particularly pointed out that: in the following examples, the specific conditions are not specified, and the conventional conditions or the conditions recommended by the manufacturer are used, and the raw materials used in the following examples can be obtained from ordinary market sales unless otherwise specified.

[0035] The nano ZrC ceramic powder is purchased from Beijing Ji'an Heng Technology Co., Ltd., the product number is 20121129202015, the purity is ≥99.9wt%, the particle size is 0-30nm, it belongs to cubic crystal type, and it is black powder. The nano ZrN ceramic powder is purchased from Beijing Ji'an Heng Technology Co., Ltd., the product number is 20121129205644, the purity is ≥99.9wt%, the particle size is 0-100nm, it belongs to tetragonal crystal type, and it is dark yellow powder.

[0036] Preparation example of MgO·1.1Al2O3 powder

[0037] Preparation example

[0038] The preparation method of the MgO·1.1Al2O3 powder is as follows:

[0039] Step I, Mg(NO3)2·6H2O and Al(NO3)3·9H2O are mixed in a molar ratio of 1:2.2 in deionized water, stirred for 1h, and a clear nitrate solution is obtained; a citric acid solution is prepared for standby.

[0040] Step II, slowly add the citric acid solution to the nitrate solution, the total amount of the citric acid solution is added so that the molar ratio of citric acid to metal cation is 1:1, then continuously stir at 60℃ for 2h, and the continuous stirring is to avoid the formation of precipitate. Then add ammonia water to adjust the pH value of the mixed solution to about 5.0, and then place the solution in a drying oven, dry at 148℃, and as the solvent volatilizes, the solution gradually becomes a high-viscosity gel, and then becomes a translucent dry gel.

[0041] Step III, ignite the dry gel in a muffle furnace at a temperature of 300℃, and after combustion, black fluffy ash is formed, which is ground to obtain MgO·1.1Al2O3 precursor. The MgO·1.1Al2O3 precursor is calcined in a muffle furnace at a temperature of 750℃ for 2.0h to obtain MgO·1.1Al2O3 powder.

[0042] Example

[0043] Example 1

[0044] The raw material of the ceramic composite material is 100 mL of MgO·1.1Al2O3 powder and 8 mL of zirconium ceramic powder. The zirconium ceramic powder is obtained by uniformly mixing 4 mL of nano ZrC ceramic powder and 4 mL of nano ZrN ceramic powder. The MgO·1.1Al2O3 powder is prepared by the method of the preparation example.

[0045] The preparation method of the ceramic composite material is as follows:

[0046] Step S1, uniformly mix 100 mL of MgO·1.1Al2O3 powder and 4.8 mL of zirconium ceramic powder, and then place it on a tablet press to press at a pressure of 350 MPa for 10 min to obtain an initial ceramic body.

[0047] Step S2, place the ceramic body in a muffle furnace and calcine at 1700°C for 2.0 h to obtain an initial ceramic composite material.

[0048] Step S3, crush the initial ceramic composite material into a powder, then add 3.2 mL of zirconium ceramic powder, mix uniformly, and then place it on a tablet press to press at a pressure of 350 MPa for 10 min to obtain a reset ceramic body.

[0049] Step S4, place the reset ceramic body in a muffle furnace and calcine at 1700°C for 2.0 h to obtain a ceramic composite material.

[0050] Example 2

[0051] The difference between Example 2 and Example 1 is that the raw material ratio of the composite ceramic is different, which is as follows:

[0052] In Example 2, the raw material for preparing the ceramic composite material is 100 mL of MgO·1.1Al2O3 powder and 5 mL of zirconium ceramic powder. The zirconium ceramic powder is obtained by uniformly mixing 2.5 mL of nano ZrC ceramic powder and 2.5 mL of nano ZrN ceramic powder.

[0053] The preparation method of the composite ceramic is:

[0054] Step S1, uniformly mix 100 mL of MgO·1.1Al2O3 powder and 3 mL of zirconium ceramic powder, and then place it on a tablet press to press at a pressure of 350 MPa for 10 min to obtain an initial ceramic body.

[0055] Step S2 is the same as Example 1.

[0056] Step S3, after the initial ceramic composite material is crushed into powder, 2 mL of zirconium ceramic powder is added, and after being mixed uniformly, it is placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic body.

[0057] Step S4 is the same as in Example 1.

[0058] Example 3

[0059] The difference between Example 3 and Example 1 is that the raw materials for preparing the composite ceramic are different, which are as follows:

[0060] In Example 3, the raw materials for preparing the ceramic composite material are: 100 mL of MgO·1.1Al2O3 powder and 10 mL of zirconium ceramic powder. The zirconium ceramic powder is obtained by uniformly mixing 5 mL of nano-ZrC ceramic powder and 5 mL of nano-ZrN ceramic powder.

[0061] The preparation method of the composite ceramic is as follows:

[0062] Step S1, 100 mL of MgO·1.1Al2O3 powder and 6 mL of zirconium ceramic powder are uniformly mixed and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic body.

[0063] Step S2 is the same as in Example 1.

[0064] Step S3, after the initial ceramic composite material is crushed into powder, 2 mL of zirconium ceramic powder is added, and after being mixed uniformly, it is placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic body.

[0065] Step S4 is the same as in Example 1.

[0066] Example 4

[0067] The raw materials of the ceramic composite material are the same as in Example 1. The difference between this embodiment and Example 1 is that when preparing the ceramic composite, in steps S1 and S3, the zirconium ceramic powder is also added twice, but the amount of zirconium ceramic powder selected in the two additions is different.

[0068] The preparation method of the ceramic composite material is as follows:

[0069] Step S1, 100 mL of MgO·1.1Al2O3 powder and 4.4 mL of zirconium ceramic powder are uniformly mixed and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic body.

[0070] Step S2 is the same as in Example 1.

[0071] Step S3, after the initial ceramic composite material is crushed into powder, 3.6 mL of zirconium ceramic powder is added, and after being mixed uniformly, it is placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic body.

[0072] Step S4 is the same as in Example 1.

[0073] Example 5

[0074] The raw materials of the ceramic composite material are the same as in Example 1. The difference between this embodiment and Example 1 is that, in the preparation of the ceramic composite, the zirconium ceramic powder is also added twice in steps S1 and S3, but the amount of zirconium ceramic powder selected for the two additions is different.

[0075] The method for preparing the ceramic composite material is as follows:

[0076] Step S1, 100 mL of MgO·1.1Al2O3 powder and 5.2 mL of zirconium ceramic powder are mixed uniformly and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic body.

[0077] Step S2 is the same as in Example 1.

[0078] Step S3, after the initial ceramic composite material is crushed into powder, 3.6 mL of zirconium ceramic powder is added, and after being mixed uniformly, it is placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic body.

[0079] Step S4 is the same as in Example 1.

[0080] Comparative Example

[0081] The difference between Comparative Example 1-2 and Example 1 is that the raw materials for preparing the composite ceramic are different, as follows:

[0082] Comparative Example 1

[0083] In Comparative Example 1, the raw materials for preparing the ceramic composite material are 100 mL of MgO·1.1Al2O3 powder and 3 mL of zirconium ceramic powder. The zirconium ceramic powder is obtained by uniformly mixing 1.5 mL of nano-ZrC ceramic powder and 1.5 mL of nano-ZrN ceramic powder.

[0084] The method for preparing the composite ceramic is as follows:

[0085] Step S1, 100 mL of MgO·1.1Al2O3 powder and 1.8 mL of zirconium ceramic powder are mixed uniformly and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic body.

[0086] Step S2 is the same as in Example 1.

[0087] Step S3, after the initial ceramic composite material is crushed into powder, 1.2 mL of zirconium ceramic powder is added, and after being uniformly mixed, it is placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic body.

[0088] Step S4 is the same as in Example 1.

[0089] Comparative Example 2

[0090] In Comparative Example 2, the raw materials for preparing the ceramic composite material are 100 mL of MgO·1.1Al2O3 powder and 12 mL of zirconium ceramic powder. The zirconium ceramic powder is obtained by uniformly mixing 6 mL of nano-ZrC ceramic powder and 6 mL of nano-ZrN ceramic powder.

[0091] The preparation method of the composite ceramic is as follows:

[0092] Step S1, 100 mL of MgO·1.1Al2O3 powder and 7.2 mL of zirconium ceramic powder are uniformly mixed and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic body.

[0093] Step S2 is the same as in Example 1.

[0094] Step S3, after the initial ceramic composite material is crushed into powder, 4.8 mL of zirconium ceramic powder is added, and after being uniformly mixed, it is placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic body.

[0095] Step S4 is the same as in Example 1.

[0096] Comparative Example 3

[0097] The difference between this comparative example and Example 1 is that the zirconium ceramic powder is only nano-ZrC ceramic powder and does not contain nano-ZrN ceramic powder; the others are the same as in Example 1.

[0098] Comparative Example 4

[0099] The difference between this comparative example and Example 1 is that the zirconium ceramic powder is only nano-ZrN ceramic powder and does not contain nano-ZrC ceramic powder; the others are the same as in Example 1.

[0100] Comparative Example 5

[0101] The raw materials for the ceramic composite material are the same as in Example 1. The difference between this comparative example and Example 1 is that in the preparation of the ceramic composite, the zirconium ceramic powder is also added twice in steps S1 and S3, but the amount of zirconium ceramic powder selected for the two additions is different.

[0102] The preparation method of the ceramic composite material is as follows:

[0103] Step S1, 100 mL MgO-1.1Al203powder and 4 mL zirconium ceramic powder were mixed uniformly and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic green body.

[0104] Step S2 was the same as in Example 1.

[0105] Step S3, after the initial ceramic composite material was crushed into powder, 4 mL of zirconium ceramic powder was added, and after being mixed uniformly, it was placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic green body.

[0106] Step S4 was the same as in Example 1.

[0107] Comparative Example 6

[0108] The raw materials of the ceramic composite material were the same as in Example 1. The difference between this example and Example 1 is that when preparing the ceramic composite, the zirconium ceramic powder is also added twice in steps S1 and S3, but the amount of zirconium ceramic powder selected in the two additions is different.

[0109] The preparation method of the ceramic composite material is as follows:

[0110] Step S1, 100 mL MgO-1.1Al203powder and 5.6 mL zirconium ceramic powder were mixed uniformly and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic green body.

[0111] Step S2 was the same as in Example 1.

[0112] Step S3, after the initial ceramic composite material was crushed into powder, 2.4 mL of zirconium ceramic powder was added, and after being mixed uniformly, it was placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain a reset ceramic green body.

[0113] Step S4 was the same as in Example 1.

[0114] Comparative Example 7

[0115] The difference between this comparative example and Example 1 is that the ceramic composite material is only sintered once; the specific process is as follows:

[0116] The preparation method of the ceramic composite material is as follows:

[0117] Step A, 100 mL MgO-1.1Al203powder and 8 mL zirconium ceramic powder were mixed uniformly and then placed on a tablet press to be pressed at a pressure of 350 MPa for 10 min to obtain an initial ceramic green body.

[0118] Step B, the ceramic green body was placed in a muffle furnace and calcined at 1700°C for 2.0h to obtain the ceramic composite material.

[0119] Comparative Example 8

[0120] The difference between this comparative example and Example 1 is that the entire zirconium ceramic powder is added only at the first sintering when preparing the ceramic composite material; the details are as follows:

[0121] The method for preparing the ceramic composite material is as follows:

[0122] Step a, 100mL of MgO·1.1Al2O3 powder and 8mL of zirconium ceramic powder were mixed uniformly and then placed on a tablet press to be pressed at a pressure of 350MPa for 10min to obtain an initial ceramic green body.

[0123] Step b, the ceramic green body was placed in a muffle furnace and calcined at 1700°C for 2.0h to obtain an initial ceramic composite material.

[0124] Step c, the initial ceramic composite material was crushed into powder and then placed on a tablet press to be pressed at a pressure of 350MPa for 10min to obtain a reset ceramic green body.

[0125] Step d, the reset ceramic green body was placed in a muffle furnace and calcined at 1700°C for 2.0h to obtain a ceramic composite material.

[0126] Comparative Example 9

[0127] The difference between this comparative example and Example 1 is that the ceramic composite material is prepared only once without adding zirconium ceramic powder; the details are as follows:

[0128] The method for preparing the ceramic composite material is as follows:

[0129] Step 1, 100mL of MgO·1.1Al2O3 powder was placed on a tablet press and pressed at a pressure of 350MPa for 10min to obtain an initial ceramic green body.

[0130] Step 2, the ceramic green body was placed in a muffle furnace and calcined at 1700°C for 2.0h to obtain a ceramic composite material.

[0131] Performance detection

[0132] The Vickers hardness of the material was detected according to the relevant requirements of ASTM C1327-15 “Standard Test Method for Vickers Indentation Hardness of Advanced Ceramics, Standard”. The specific results are shown in Table 1.

[0133] Table 1 Hardness of different ceramic materials

[0134] Embodiment Example 1 Example 2 Example 3 Example 4 Example 5 Vickers Hardness (GPa) 28.2 27.5 28.1 27.9 27.6 Embodiment Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Vickers Hardness (GPa) 24.8 26.6 24.6 24.3 25.8 Embodiment Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Vickers Hardness (GPa) 25.2 25.4 25.2 22.2

[0135] Comparing the data of Table 1 and Comparative Example 9, it is found that the hardness of the ceramic composite material of the present application is significantly improved, and the hardness is in the range of 27.4-28.2 GPa. By comparing the data of Example 1, Examples 2-3 and Comparative Examples 1-2, it is found that the ratio of the amount of MgO·1.1Al2O3 powder and zirconium-based ceramic powder has a great influence on the hardness of the material when preparing the ceramic composite material. The main reason is that the ratio of the amount of raw materials affects the crystal phase distribution and the density of the material, thereby affecting the hardness of the material.

[0136] The results of Example 1 and Comparative Examples 3-4 show that the zirconium-based ceramic powder is a mixture of nano-ZrC ceramic powder and nano-ZrN ceramic powder, which has a positive effect on MgO·1.1Al2O3 to improve the hardness of the material. The possible reason is that the crystal phase of MgO·1.1Al2O3 is Zr(C,N) solid solution, so that when only nano-ZrC ceramic powder or only nano-ZrN ceramic powder is used to modify MgO·1.1Al2O3, the desired effect of improving the hardness of the ceramic composite material cannot be achieved.

[0137] The results of Example 1, Examples 4-5 and Comparative Examples 5-8 show that not only the ratio of raw materials affects the hardness of the material, but also the preparation method has a great influence on the hardness of the material. Among them, Example 1 and Comparative Examples 7-8 show that when preparing the ceramic composite material, it is recommended to use the twice sintering method; and the zirconium-based ceramic powder should be added in two batches during the two sintering processes, so that the ceramic composite material can obtain excellent hardness. In addition, as shown in the results of Example 1, Examples 4-5 and Comparative Examples 5-6, when the zirconium-based ceramic powder is added in two batches during the two sintering processes, the amount of addition is also important, which has a great influence on the hardness of the ceramic composite material. The possible reason is that the twice sintering + twice batch addition of zirconium-based ceramic powder can first densify the ceramic composite material through the twice sintering, and then make the zirconium-based ceramic powder and MgO·1.1Al2O3 powder contact more uniformly, which has a greater influence on the crystal phase of MgO·1.1Al2O3, and finally brings more significant positive effect on the hardness of the ceramic composite material.

[0138] The specific embodiments are only an explanation of the present application, and are not a limitation of the present application. Those skilled in the art can make modifications to the embodiments without creative contribution after reading the specification, as long as the modifications are within the scope of the claims of the present application.

Claims

1. A ceramic composite material, characterized by, The ceramic composite material comprises the following components: MgO·1.1Al2O3 powder and zirconium ceramic powder accounting for 5-10% of the volume of the MgO·1.1Al2O3 powder; The zirconium ceramic powder comprises the following components in volume percentage: 45-55% of nano ZrC ceramic powder and the balance of nano ZrN ceramic powder; The preparation method of the ceramic composite material comprises the following steps: Step S1, uniformly mixing all the MgO·1.1Al2O3 powder and 55-65 Vol.% of the zirconium ceramic powder and then pressing to obtain an initial ceramic green body; Step S2, sintering the ceramic green body to obtain an initial ceramic composite material; Step S3, crushing the initial ceramic composite material into powder, adding the remaining 35-45 Vol.% of the zirconium ceramic powder, uniformly mixing and then pressing to obtain a reset ceramic green body; Step S4, sintering the reset ceramic green body to obtain a ceramic composite material.

2. A ceramic composite material according to claim 1, characterised in that The preparation method of the MgO·1.1Al2O3 powder comprises the following steps: Step I, mixing Mg(NO3)2·6H2O and Al(NO3)3·9H2O in a molar ratio of 1:2.2 and stirring to obtain a clear nitrate solution; preparing a citric acid solution for standby; Step II, adding the citric acid solution dropwise into the nitrate solution, continuously stirring at 55-65℃, adjusting the pH value of the nitrate solution to 4.5-5.3, and drying to obtain a dry gel; Step III, burning and crushing the dry gel to obtain MgO·1.1Al2O3 precursor, calcining the MgO·1.1Al2O3 precursor at 700-800℃ for 1.5-2.5h to obtain MgO·1.1Al2O3 powder.

3. A ceramic composite material according to claim 2, characterised in that The drying temperature in step II is 140-155℃.

4. A ceramic composite material according to claim 2, wherein The ambient temperature when the dry gel is burned in step III is 280-320℃.

5. The ceramic composite material of claim 1, wherein The nano ZrC ceramic powder particle size D ZrC is: 0 < D ZrC ≤ 30 nm, purity ≥ 99.9 wt%.

6. The ceramic composite material of claim 1, wherein The nano ZrN ceramic powder particle size D ZrN is: 0 < D ZrN ≤ 100 nm, purity ≥ 99.9 wt%.

7. The ceramic composite material of claim 1, wherein, The pressure applied during the pressing process in step S1 is 300-400MPa; the pressure applied during the pressing process in step S3 is 300-400MPa.

8. The ceramic composite material of claim 1, wherein, The sintering process in step S2 comprises: calcining the ceramic green body at 1600-1800℃ for 1.5-2.5h; the sintering process in step S4 comprises: calcining the ceramic green body at 1600-1800℃ for 1.5-2.5h.

Citation Information

Patent Citations

  • Fluorescent ceramic and preparation method thereof

    CN110240468A

  • Spinel ceramics

    JP1986086466A